PERAN PEMIMPIN SEBAGAI PEMBERDAYA DAN MOTIVATOR ANGGOTA DI DIREKTORAT RESERSE NARKOBA POLDA JAWA TENGAH - Eki Pavitarani, Distya; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2013)
Recruitmen process and placement of personnel in the Directorate of Central Java Police Drug Investigation Division, has not describe personnel needs, in determining which members of the Directorate of Central Java Police Narcotics Investigation Unit received only members provided by the bureau of human resources. Another phenomenon that occurs in Directorate of Central Java Police Drug Investigation Division are declining morale member in carrying out duties, which have an impact on performance. This study aims to identify and determine the role of leaders in improving the performance of organizations in the Directorate of Central Java Police Drug Investigation Division. Research questions were examined in this study were (1) How does the role of the leader in empowering existing members and placing members in accordance with their competence to fill the right positions? (2) How does a leader in efforts to motivate and inspire its members to improve performance? (3) What is the role of leadership in seeking alternative solutions to the barriers that exist in the performance of the Directorate of Central Java Police Narcotics Investigation?The researchÂ uses qualitative research methods where data collection is done through depth interviews, observations, and documentation that are better able to explore the role of the leader in Drug Investigation Directorate. Validity of the data used is to implement member checking. This study took place at the Directorate of Central Java Police Narcotics Investigation and retrieve objects members and leaders who served in the Directorate of Central Java Police Drug Investigation Division.In this study revealed that the role of leaders in Drug Investigation Directorate in the Central Java Police empower existing members to the fullest. Leaders put members of the right to occupy a position tailored to vocational education has been followed. Drug Investigation Division in the Directorate itself, the Leader has the authority to determine who attend training or vocational education held by the bureau of human resources. In addition, the leaders also held Rakernis which aims to provide training to members on the subject of drug offenses and how to resolve the problem, and to motivate members to get the better performance provided. Leadership role to foster or strengthen motivation to members by giving awards if the performance of a given good and proud member of the institution. The award is given to members in the form of a promotion, or a chance to go to school anymore. Besides other forms of motivation in the form of attention and a real example to the members that can be used as an example in everyday life. In addition, members are given discretion in carrying out the task, as the leader of the task entrusted to members and assume that the member is able to do the job well. While in the process of decision-making and problem-solving, leadership involves its members in accordance with the issues involved, the level of confidentiality, duty and authority so that not all of them are involved in any decision making. Besides always received an opinion leader for the betterment and improvement of the performance of the Directorate of Central Java Police Drug Investigation Division.Â